JEHD 2017
DOI: 10.15640/jehd.v6n3a6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Organizational Commitment Moderated by Job Satisfaction: What Can We Learn from Indonesia?

Abstract: This quantitative research aims to analyze discreet and simultaneous effect of school climate, reward system, value orientation toward job satisfaction and organizational commitment. It also analyzes the indirect effect of school climate, reward system and value orientation toward organizational commitment through job satisfaction of public middle school teachers at North Minahasa regency, Indonesia. Data are taken from a survey to 216 teachers from 15 middle schools, and analyzed using regression and path ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…And fostering this interaction should remain on the behaviour of each party. Previous studies had linked the effect of school climate toward organisational commitment directly and indirectly through job satisfaction (Lotulung, Senduk, Kambey & Paturusi, 2017). Studies of factors of organisational commitment usually paired school climate along with other variable as predictors (Agung, 2009 Raharjo & Nafisah, 2006;Rahmi, 2013;Seniati, 2006;Situmorang, 2012) Although studies had confirmed that school climate as a significant predictor of organisational commitment, there is a need to see which components of school climate yield significant and more prominent contribution.…”
Section: Introductionmentioning
confidence: 99%
“…And fostering this interaction should remain on the behaviour of each party. Previous studies had linked the effect of school climate toward organisational commitment directly and indirectly through job satisfaction (Lotulung, Senduk, Kambey & Paturusi, 2017). Studies of factors of organisational commitment usually paired school climate along with other variable as predictors (Agung, 2009 Raharjo & Nafisah, 2006;Rahmi, 2013;Seniati, 2006;Situmorang, 2012) Although studies had confirmed that school climate as a significant predictor of organisational commitment, there is a need to see which components of school climate yield significant and more prominent contribution.…”
Section: Introductionmentioning
confidence: 99%